Perinuclear positioning of endosomes can affect PS-ASO activities. Issue 22 (8th December 2021) - Liang, Xue-hai; Nichols, Joshua G; Tejera, Dario; Crooke, Stanley T
Abstract: Phosphorothioate (PS) modified antisense oligonucleotide (ASO) drugs that act on cellular RNAs must enter cells and be released from endocytic organelles to elicit antisense activity. It has been shown that PS-ASOs are mainly released by late endosomes. However, it is unclear how endosome movement in cells contributes to PS-ASO activity. Here, we show that PS-ASOs in early endosomes display Brownian type motion and migrate only short distances, whereas PS-ASOs in late endosomes (LEs) move linearly along microtubules with substantial distances. In cells with normal microtubules and LE movement, PS-ASO-loaded LEs tend to congregate perinuclearly. Disruption of perinuclear positioning of LEs by reduction of dynein 1 decreased PS-ASO activity, without affecting PS-ASO cellular uptake. Similarly, disruption of perinuclear positioning of PS-ASO-LE foci by reduction of ER tethering proteins RNF26, SQSTM1 and UBE2J1, or by overexpression of P50 all decreased PS-ASO activity. However, enhancing perinuclear positioning through reduction of USP15 or over-expression of RNF26 modestly increased PS-ASO activity, indicating that LE perinuclear positioning is required for ensuring efficient PS-ASO release. Together, these observations suggest that LE movement along microtubules and perinuclear positioning affect PS-ASO productive release.